2015
DOI: 10.1186/s12938-015-0006-8
|View full text |Cite
|
Sign up to set email alerts
|

EEG based evaluation of stereoscopic 3D displays for viewer discomfort

Abstract: BackgroundConsumer preference is rapidly changing from 2D to 3D movies due to the sensational effects of 3D scenes, like those in Avatar and The Hobbit. Two 3D viewing technologies are available: active shutter glasses and passive polarized glasses. However, there are consistent reports of discomfort while viewing in 3D mode where the discomfort may refer to dizziness, headaches, nausea or simply not being able to see in 3D continuously.MethodsIn this paper, we propose a theory that 3D technology which project… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…demanding different cognitive processing despite the fact they both depict the same content (information). The computational non-equivalency in virtual 3D viewing was supported also on the neuroscientific level, where extra visual cues included in the perceived scene aroused brain activity [25]. Studies on 3D visualization show enthusiasm on one hand and certain doubts on the other especially with respect to a user-friendly human-computer interaction.…”
Section: Real 3d and Pseudo 3d Visualization And Geovisualizationmentioning
confidence: 94%
“…demanding different cognitive processing despite the fact they both depict the same content (information). The computational non-equivalency in virtual 3D viewing was supported also on the neuroscientific level, where extra visual cues included in the perceived scene aroused brain activity [25]. Studies on 3D visualization show enthusiasm on one hand and certain doubts on the other especially with respect to a user-friendly human-computer interaction.…”
Section: Real 3d and Pseudo 3d Visualization And Geovisualizationmentioning
confidence: 94%
“…In [12], the researchers claimed that the behavior of brain signals did not change during 2D/3D TV watching. With the opposite result of this study, brain dynamics have been shown to exhibit different behaviors in the brain lobes and EEG frequency bands [49], [48], [5], [10]. Analysis of brain signals by watching 2D and 3D videos individually was done extensively in our previous studies [5], [10].…”
Section: Discussionmentioning
confidence: 97%
“…Reviewing the studies on 2D and 3D technology, no detailed quantitative research was found using the channels representing the five lobes of the brain and all EEG bands [47], [8], [9]. The effect of watching 2D and 3D TV on brain signals has been the focus of some studies in terms of qualitative [12], [48]. In [12], the researchers claimed that the behavior of brain signals did not change during 2D/3D TV watching.…”
Section: Discussionmentioning
confidence: 99%
“…This may be explained by differences in the neural processing of the two image types. A recent study using electroencephalography (EEG) compared the brainwave activity of individuals when they viewed 3D movies using a passive 3D projection system and 2D images 14 . The study found statistically significant higher brainwave activity in the beta, delta, and gamma bands for 2D images and in the alpha and theta bands during 3D projection.…”
Section: Discussionmentioning
confidence: 99%